Lessons from a Book in Alba Iulia Tamás Balásfi: Epinicia, 1616 - Ajkay Alinka (Hungarian Studies Yearbook)
The only complete copy of Tamás Balásfi’s Epinicia Benedicto Nagi known today is preserved among the old books at the Batthyaneum in Alba Iulia (Gyulafehérvár). This work was published in Pozsony in 1616. According to current knowledge, only three copies of this small volume, consisting of about forty pages, have survived. The copy in the Hungarian National Library is missing the entire first sheet (A), including the title page and dedication, as well as two pages from the end. This small book is particularly significant for the study of Péter Pázmány’s controversial writings before his archbishopric, representing the final piece in a series of polemics (1614–1616) written against the Lutherans of Western Transdanubia. Pázmány became archbishop in 1616 and was either unable or unwilling to continue engaging in this controversy, leaving Tamás Balásfi to conclude the polemic on his behalf. At the end of this paper, I will provide a transcription of a missing part from the Budapest copy: the Latin dedication at the beginning of the book.